2008
DOI: 10.1589/jpts.20.191
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Neurophysiological Modification after Peripheral Neuronal Sensitization

Abstract: Abstract. [Purpose] It is known that peripheral noxious events provoke sensitization of the peripheral and spinal nervous systems and influence neural transmissions to the brain. In this study, we aimed to examine how brain activation is affected when provoked by electrical stimulation and by prior sensitization with peripheral application of a painful agent (capsaicin).[Subjects] Six normal adult volunteers were enrolled in this study.[Methods] Pain intensity of participants was reported using a visual analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, previous studies 22 , 23 , 24 ) have shown the same tendency. The reasons may include analgesia to central sensitization 26 , 27 , 28 ) , the descending pain modulatory system 24 , 34 , 35 ) , DNIC 25 ) , and release of endogenous opioid peptides 35 , 36 ) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, previous studies 22 , 23 , 24 ) have shown the same tendency. The reasons may include analgesia to central sensitization 26 , 27 , 28 ) , the descending pain modulatory system 24 , 34 , 35 ) , DNIC 25 ) , and release of endogenous opioid peptides 35 , 36 ) .…”
Section: Discussionmentioning
confidence: 99%
“…TENS has been used as an analgesic treatment for central sensitization induced by pain stimulus, and the effects have been reported 26 , 27 , 28 ) . The analgesic effects of the treatment to central sensitization is based on TENS to the site of pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are no published reports that discuss the effects of TENS applied simultaneously to the site contralateral to the site of pain and to the neck at the same dermatome level as the site of pain. Moreover, almost no current reports discuss the relationship between changes in pain and brain activity after TENS 6 ) .…”
Section: Introductionmentioning
confidence: 99%